Math CentralQuandaries & Queries


Subject: The Elimination Method
Name: addrianna
Who are you: Student



Here's an example: x - 9 = y and 3x + 2y = 4

x - 9 = y becomes x = y + 9.
3x + 2y = 4 becomes x = (4 - 2y) / 3

So that means y + 9 = (4 - 2y) / 3. We've eliminated x. We could as easily have chosen to eliminate y rather than x - you just pick what's convenient.

Now you can solve this last one for the value of y. Once you know the value of y, substitute that into either one of the original equations and find x. It doesn't matter which of the two original equations you choose, because both will give you the same value of x.

That's how you can use the elimination method to solve these "simultaneous" equations.

Hope this helps,
Stephen La Rocque.

About Math Central


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences.
Quandaries & Queries page Home page University of Regina PIMS